ANALISIS DAN PEMODELAN SISTEM INFORMASI PENGAJUAN ALAT DAN BAHAN LABORATORIUM POLITEKNIK JAMBI - Tanto, Tanto (JURNAL AKADEMIKA, 2017)
Laboratory of the Politeknik Jambi provide facilities and equipment for Lecturers and Students in the lab. Procedure filing process tool and materials lab at the Politeknik Jambi Laboratory unit includes filing, checks, purchase and distribution of items needed during the practicum. But at the time of administration, procurement is not good, because every unit in filing administrative tools and materials lab with a format that is different. This research resulted in a filing information system modeling tools and lab materials Politeknik Jambi Modeling using techniques Unified Modeling Language (UML) withdiagrams, use case diagrams. activity and class diagrams modeling is used as a reference in building information systems that include procurement of laboratory equipment and materials, in order to assist existing problems, in accordance with established standards.